VIRTUAL CLASS FOR STUDENTS’ INDIVIDUAL TRAINING ORGANIZATION (Journal of Information Technologies in Education (ITE), 2011)
In the article the problem of modernization of individual studies of students rises by modern facilities of computer-reference educational environment. The criteria of determination of level of ІКТ-компетентності of teachers-предметників which work with a virtual class are given, the model of integration of virtual class is described in an educational-educate process. Research of virtual class is in-process presented as a computer-reference educational environment.
Keywords: computer-reference educational environment; conferencing; IKT; individual studies; virtual class; web-conference